Uterus Didelphys: Report of a Puerperal Torsion and a Review of the Literature - Lucio M. A. Cipullo; Slobodan Milosavljevic; Elisabeth D. van Oudgaarden (Case Reports in Obstetrics and Gynecology)
A 29-year-old Para 2 was admitted to the emergency department with increasing lower abdominal pain. The patient had undergone an uncomplicated elective repeat caesarean section 7 days before being admitted to the emergency department. An emergency laparotomy revealed a uterus didelphys with a torsion of one of the uteri.